Review on grid-forming converter control methods in high-proportion renewable energy power systems - Yuting Teng; Wei Deng; Wei Pei; Yifeng Li; Li Dingv; Hua Ye (Global Energy Interconnection, 2022)
Grid-forming (GFM) converters can provide inertia support for power grids through control technology, stabilize voltage and frequency, and improve system stability, unlike traditional grid-following (GFL) converters. Therefore, in future “double high” power systems, research on the control technology of GFM converters will become an urgent demand. In this paper, we first introduce the basic principle of GFM control and then present five currently used control strategies for GFM converters: droop control, power synchronization control (PSC), virtual synchronous machine control (VSM), direct power control (DPC), and virtual oscillator control (VOC). These five strategies can independently establish voltage phasors to provide inertia to the system. Among these, droop control is the most widely used strategy. PSC and VSM are strategies that simulate the mechanical characteristics of synchronous generators; thus, they are more accurate than droop control. DPC regulates the active power and reactive power directly, with no inner current controller, and VOC is a novel method under study using an oscillator circuit to realize synchronization. Finally, we highlight key technologies and research directions to be addressed in the future.